The role of American Christian and Japanese Buddhist clergy in suicide prevention a comparison of different religious and cultural approaches to counseling - Hirono, Tatsushi (Lewiston, N.Y. : Edwin Mellen Press, 2012)
The purpose of this study is to examine American and Japanese clergy's perception of their role in the prevention of suicide. The research questions are: (1) How do clergy in the US and Japan perceive suicide?; (2) Do they see suicide differently?; and (3) How do they envision the role of suicide prevention? The hypotheses are: (A) Christian clergy think that suicide is an unacceptable "sin;" (B) Buddhist clergy are more accepting of suicide than Christian clergy; and (C) There are role differences related to suicide prevention in the Japanese and American religious communities; and (D) Americ.
Chapter 1. The role of the clergy -- Chapter 2. Using both quantitative and qualitative methods -- Chapter 3. Clergy's views on prevention, obligation, sin, counseling, and resources: results of the quantitative analysis -- Chapter 4. Analyzing "why" and "where" cultural/religious differences came from: results of the qualitative questions -- Chapter 5. Discussion by analyzing close-ended questions -- Chapter 6. Discusssion by analyzing open-ended questions -- Chapter 7. Conclusion: policy implications and limitation of this research -- Bibliography -- Index.
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Suicide -- United States -- Prevention; Suicide -- Japan -- Prevention; Pastoral counseling -- United States; Pastoral counseling -- Japan; Leadership -- Religious aspects; Pastoral counseling -- Japan; Pastoral counseling -- United States; Suicide -- Japan -- Prevention; Suicide -- United States -- Prevention; Religion; RELIGION / Counseling; PSYCHOLOGY / Suicide; Electronic books